CLINICAL MANIFESTATIONS OF DELIRIUM IN ELDERLY - Inche Mat, Liyana Najwa; Sulaiman, Wan Aliaa Wan; Kee, Hoo Fan; Baharin, Muhammad Afwan Shamsul; Ghenesan, Surendran; Ishak, Siti Nabila; Abidin, Wan Fairuzlina Zainal; Daud, Nor Liyana Farhan; Yun, Tan Hong (Malang Neurology Journal, 2018)
Delirium is commonly encountered in the elderly. It is important to recognize and subsequently treat delirium early to prevent morbidity and mortality. The primary objective of this article review is to gather specific information about each clinical manifestation of delirium in elderly. Sieving through numerous literature and studies regarding the topic of Delirium in the elderly. Majority of the article source were from Medline and PubMed as subscribed by the institution where there are more than 27 million citations in the field of biomedical articles. The articles include articles that was published in Malaysia and also international article due to the limitation in Malaysia itself. The articles were retrieved from publications in the year 1992 up to the current year 2017. Clinical manifestation of delirium that had been reviewed include disordered thinking, euphoric, language impairment, illusion, reversal of sleep wake cycle, inattention, disoriented and memory deficit. Most of the information is about prevalence, clinical diagnosis, and pathophysiology of each of the clinical manifestation. Delirium in elderly is very complex and complicated which involve physical, emotion feelings not only for the patient but also for people in their surroundings. Many articles reviewed explain about each of the symptoms in further details in term on how they act and how they interact with people surrounding.